Relative frequencies of supernovae versus properties of spiral hosts. Issue Volume 9:Issue S304(2013) (25th July 2014) - Hakobyan, A. A.; Nazaryan, T. A.; Adibekyan, V. Zh.; Petrosian, A. R.; Aramyan, L. S.; Kunth, D.; Mamon, G. A.; de Lapparent, V.; Bertin, E.; Gomes, J. M.; Turatto, M.
Abstract: In this work, we present an analysis of SNe number ratios in spiral galaxies with different morphological subtypes, luminosities, sSFR, and metallicities, to provide important information about the physical properties of the progenitor populations.